The geochemistry of Mukah and Balingan coals : a natural product approach - Farahnasya Nabilah Huda, Binti Zahari (Universiti Malaysia Sarawak, UNIMAS, 2012)
Balingan and Mukah coals were investigated for their organic geochemical contents. The coal samples were extracted sequentially on Soxhlet apparatus using dichloromethane and methanol. The crude extracts were subjected to fractionation on silica gel column chromatography into aliphatic hydrocarbon, aromatic hydrocarbon and polar organic compound fractions. These fractions were then analyzed on gas chromatography-flame ionization detector (GC-FID) and gas chromatography-mass spectroscopy (GC-MS). Analysis on aliphatic hydrocarbon fractions showed that both coals have been deposited under reducing or anoxic environment. Organic matters in Balingan and Mukah coals are thought to be originated from inland swamp and derived from marine environment. Polycyclic aromatic hydrocarbons (PAHs) data showed that both Balingan and Mukah coals are thermally immature. Several organic compounds have been successfully isolated and the significant organic compounds identified were grouped in fatty acid or ester compounds. Biomarker indices derived from distribution of hydrocarbons indicated that both coals were originated mainly from terrigenous higher plant with low thermal maturity.